Baccouche, Hatem - (:unkn) unknown (My University, 2026)
Hatem BACCOUCHE is an Engineer in Natural Resources Management graduated from the Higher School of Agriculture of Mograne (University of Carthage, Tunisia). He held the position of PRIMA Sustain-COAST project manager (www.sustain-coast.tuc.gr) at the Wastewater and Environment Laboratory of the Water Research and Technologies Center (CERTE) (www.certe.rnrt.tn/) for two years (2019 - 2021) He currently occupies the position of PRIMA InTheMED project manager (www.inthemedprima.com) in the same laboratory (CERTE).